Linking landscape structure and ecosystem service flow - Assis, Julia C. [UNESP]; Hohlenwerger, Camila; Metzger, Jean Paul; Rhodes, Jonathan R.; Duarte, Gabriela T.; da Silva, Rafaela A.; Boesing, Andrea Larissa; Prist, Paula R.; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2023)
Despite advances in understanding the effects of landscape structure on ecosystem services (ES), many challenges related to these complex spatial interactions remain. In particular, the integration of landscape effects on different components of the service provision chain (supply, demand, and flow) remains poorly understood and conceptualized. Here we propose a theoretical framework to further explore how the spatial flow of ES can vary according to landscape structure (i.e. composition and configuration) emphasizing the role played by the configuration of supply, demand, and neutral areas, as well as individual characteristics of ES (e.g., service rivalry). For this, we expand the discussion on how landscape changes can affect ES flows and propose a theoretical representation of ES flows variation led by different supply-demand ratios. Additionally, we expand this discussion by integrating the potential effects of neutral areas in the landscape as well as of supply/demand spatial overlap. This novel approach links the spatial arrangement (e.g. fragmentation, network complexity, matrix resistance) usually captured by landscape metrics, and ratios of ES supply and demand areas to potential effects on spatial flows of ES. We discuss the application of this model using widely studied ES, such as pollination, pest control by natural enemies, and microclimate regulation. Finally, we propose a research agenda to connect the presented ideas with other prominent research topics that must be further developed to support landscape management targeting ES provision. The prominence of ES science calls for contributions such as this to give the scientific community the opportunity to reflect on the underlying mechanisms of ES and avoid oversimplified spatial assessments.
Keywords: Fragmentation; Landscape configuration; Service provision chain; Spatial flow; Spatial overlap; Supply-demand ratio